2020
DOI: 10.1002/aoc.6119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and application of CoFe2O4@amino‐2‐naphthol‐4‐sulfonic acid as a novel and reusable catalyst for the synthesis of spirochromene derivatives

Abstract: In the present work, 1-amino-2-naphthol-4-sulfonic acid immobilized on functionalized CoFe 2 O 4 nanoparticles was successfully synthesized as a new, efficient, and recoverable catalyst and tested for the synthesis of spirochromene derivatives by a simple, green, and inexpensive procedure. This magnetically heterogeneous nanocatalyst was characterized by various techniques such as Fourier transform infrared (FT-IR), thermal gravimetric analysis (TGA)/derivative thermogravimetric (DTG), X-ray diffraction (XRD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The relevant synthesis in this research has already been reported in the literature. All steps have been carried out according to organic synthesis principles, such as Michael addition, water removal, and tautomerization 71 , 72 .…”
Section: Resultsmentioning
confidence: 99%
“…The relevant synthesis in this research has already been reported in the literature. All steps have been carried out according to organic synthesis principles, such as Michael addition, water removal, and tautomerization 71 , 72 .…”
Section: Resultsmentioning
confidence: 99%
“…7). This weight loss is attributed to the thermal decomposition of the xanthate complex [Ni(2-PhOEtXant)2(en)] into [NiS2], resulting in the formation of iron sulfide and volatile compounds as end products (Cordova et al, 2021), (Faroughi Niya et al, 2021) and (Palaty et al, 2010). In…”
Section: Thermogravimetric Analysis Tga Dsc and Dtamentioning
confidence: 99%
“…In this study, we continue the development of synthesizing MNPs as catalysts for multicomponent reactions (MCRs) with a focus on their environmentally‐friendly properties 45–47 . Particularly, we report on the arrangement of CoFe₂O₄@THAM@PHG‐SO₃H and explore its adequacy as a reusable nanocatalyst within the amalgamation of 3,4‐dihydropyranochromene through a three‐component response including aromatic aldehydes ( 1 ), 4‐hydroxycoumarin ( 2 ), and malononitrile ( 3 ).…”
Section: Introductionmentioning
confidence: 99%